Analysis of the Level of Education and Training on the Work Productivity of the Community Making Ulos Fabric in the Huta Raja Ulos Weaving Village - Indah Andhika Manik; Melinda Siregar; Boy Trimandez Tamba; Enda Rotua Elji Padang; Hasrita Lubis (East Asian Journal of Multidisciplinary Research, 2023)
Kampung Tenun Ulos Huta Raja developed into a village that contains cultural values, especially for the culture of the Batak people, and was rearranged by completing various infrastructures and several facilities such as clean water and sanitation, attractive landscapes, and providing training to local residents so that at the same time they This study uses quantitative research. Based on the results of data processing, the first hypothesis is rejected, which means there is a negative and significant effect of the level of education (X1) on work productivity in Ulos village. Then, based on the hypothesis testing criteria, the second hypothesis is partially accepted, which means there is a positive and significant effect of community training (X2) on work productivity in Ulos village.